Sara Gallardo. [interview]. - Peicovich, Esteban (Colección Los Palabristas, 2007)
Continuing the interview, Sara Gallardo talks with Esteban Peicovich about how her reflections on romanticism and contemplation (meditation) have influenced her writings. She talks about her life in Barcelona, her personal experiences with death because of the death of her husband, writer H.A. Murena, her expectations about her literary works, her current project, a novel titled El principio del Dr. Cardenas, and her next visit to Argentina, among other topics.